Pengaruh Teh Hijau Terhadap Fungsi Endotel Dinilai dari Flow Mediated Dilatation pada Pasien Penyakit Jantung Koroner - Faris Basalamah; Adnil Basha; Dede Kusmana (Jurnal Kardiologi Indonesia, 2007)
Background. Endothelial dysfunction begins when atherosclerosis developed as what go through on hypertension, diabetes, hyper-homocysteinemia, and also what go through among smoker who hasn’t have CAD until end phase of atherosclerosis. Impairment of endothelial function depends on vasodilatation due to the decreasing of eNOS activity. Green tea has been proved to have positive effect in reversing endothelial dysfunction among healthy smoker. This study aim to prove that the short term green tea consumption improved flow mediated dilatation among coronary artery disease patients, thus reversed endothelial dysfunction. Methods and results.Twenty three coronary artery disease patients which had been confirmed by coronary angiography joined the study. The sample was divided into two groups, first was the group who took green tea, and the second was the group who took placebo (mineral water). Before treatment, the FMD of both two groups were measured and one hour and half after treatment. After 3-7 days of treatment, both groups were crossover. FMD among healthy group of age less than 25 years old was also measured as control group. There was no significant differences in baseline characteristic between the first and the second group (both received green tea but in different time). FMD after treatment was increased among group who took green tea (4.80±5.37 vs 8.68±6.00, p=0.026), while FMD among placebo group was decreased (5.87±3.89 vs 3.34±3.66 p=0.026). There was significant differences of FMD after treatment with green tea and after treatment with placebo (8.68±6.00 vs 3.35±3.66 p = 0.002). There was no differences of brachial artery diameter in both groups (4.60±0.36 vs 4.57±0.41, p=0.8 and 4.57±0.41 vs 4.61±0.36, p=0.601). There was no significant differences on systolic and diastolic blood pressure as well as heart rate in both groups. Conclusions. Green tea had positive effect in reversing endothelial dysfunction among coronary artery disease patient by assessing flow mediated dilatation in short time. The group who took placebo showed the paradoxical effect.